A Normative Legal Analysis of the Effectiveness of Holistic Protection of Outsourcing Workers in Indonesia as a Model of Proportional Responsibility of PPJ-PJTK in the Joint and Several Liability System - Supriyanto, Supriyanto; Irayadi, Muhammad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2026)
Outsourced workers in Indonesia continue to face systemic vulnerabilities, including wage disparities, limited access to social security, and legal uncertainty resulting from fragmented responsibilities between Service User Companies (PPJ) and Manpower Service Providers (PJTK). This study aims to analyze the effectiveness of a joint and several liability model based on proportional responsibility in ensuring holistic protection for outsourced workers. The research employs a normative juridical approach through doctrinal analysis of current labor regulations, particularly the Job Creation Law and its implementing regulations, combined with a systematic literature review on outsourcing implementation challenges. Secondary data consist of statutory regulations, court decisions, and previous normative legal studies. The findings indicate that the joint and several liability model has the potential to integrate the responsibilities of PPJ and PJTK proportionally, thereby closing protection gaps related to workers’ normative rights, including wages, occupational safety and health, and access to legal remedies. This model also enhances legal certainty by allowing workers to pursue claims against both parties collectively. However, its effectiveness remains constrained by regulatory ambiguity, weak government supervision, complex litigation mechanisms, and the risk of moral hazard among manpower providers. Therefore, systemic reforms are required, including regulatory harmonization, strengthened institutional oversight, and clear operational guidelines, to achieve comprehensive protection for outsourced workers.